CsF-Promoted Iodocyclization of Allenylphosphonates: A Convenient Approach to Highly Functionalized Oxaphospholenes - Guo, Le; Gao, Yanpeng; Li, Yingjie; Wang, Yue; Li, Weilong; Chen, Shufeng (Synthesis, 2022)
A convenient CsF-promoted iodocyclization reaction of trisubstituted allenylphosphonates with iodine to construct highly functionalized oxaphospholene derivatives has been developed. A series of readily available starting materials including ferrocenylallenes, aromatic and alkyl substituted allenes can undergo the process successfully.
Keywords: ferrocene; oxaphospholenes; allenylphosphonates; iodocyclization; CsF